Analysis of the Role of Sales Promotion, Social Media Marketing, and Influencer Credibility in Driving Purchasing Decisions - Zainul Arifin; Sugiarto, Didik Priyo (Universitas Muhammadiyah Pontianak, 2026)
The rapid growth of digital marketing requires firms to identify the factors influencing consumers' purchase decisions. This study examines the effects of sales promotion, social media marketing, and influencer credibility on purchase decisions using a quantitative approach with PLS-SEM analysis of data from 120 university students in Malang. The results indicate that influencer credibility and social media marketing significantly and positively affect purchase decisions, whereas sales promotion has no significant effect. These findings suggest that firms should prioritize credible influencer collaborations and effective social media strategies to strengthen consumer purchasing decisions in the digital marketplace.